PENGARUH KARAKTERISTIK INDIVIDU, MOTIVASI DAN BEBAN KERJA TERHADAP KINERJA PEGAWAI DIRUMAH SAKIT DAERAH MADANI PROVINSI SULAWESI TENGAH (Studi Perbandingan antara Instalasi Kesehatan Jiwa dan Umum) - Amir, Amir (Katalogis, 2016)
The Influence Of Individual Characteristics, Motivation, and Workload On Personnel Performance in Madani Hospital Of Central Sulawesi This research is aimed to determinen and analyze simultaneous and partial influence of individual characteristics, motivation, and workload on personnel performance in madani hospital, central sulawesi. Respondents in this research consist of 80 people. Method of analysis used is multiple linear regressions and independent t test.The result shows that simultaneously, individual characteristics, motivation, and workload influence the performance of personnel in Madani Hospital. Partially, individual characteristics has insignificant influence on personnel performance, while motivation and workload have positive and significant influence. In addition, The result of the t test indicates that individual characteristics, motivation, and workload have significant influence on theÂ performanceÂ of personnel both in mental health department and general wellness department in Madani Hospital of Central Sulawesi.